2020
DOI: 10.1111/php.13334
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hypotaurine in Protection against UVA‐Induced Damage in Keratinocytes

Abstract: Photoageing and skin cancer are major causes of morbidity and are a high cost to society. Interest in the development of photoprotective agents for inclusion in topical cosmetic and sunscreen products is profound. Recently, amino acids with a sulfinic group, notably hypotaurine, have been included as ingredients in cosmetic preparations. However, the mechanism of action of hypotaurine as a possible anti‐aging agent is unknown, despite its use as a free radical scavenger. To address this issue, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…(11)(12)(13)(14)(15) HTAU protects cells from H 2 O 2 induced damage and ultraviolet light (UV) irradiation. (16,17) These reports support the potential for TTAU and HTAU protection against ionizing radiation damage.…”
mentioning
confidence: 61%
“…(11)(12)(13)(14)(15) HTAU protects cells from H 2 O 2 induced damage and ultraviolet light (UV) irradiation. (16,17) These reports support the potential for TTAU and HTAU protection against ionizing radiation damage.…”
mentioning
confidence: 61%
“…Allium plants such as garlic ( Allium sativum , Liliaceae) produce S-allyl cysteine (SAC; S-hydrocarbyl-L-cysteine) (Figure 1) (NCBI, 2022a), an organosulfur amino acid (Aziz, Ramalingam, Latip, & Zainalabidin, 2021). Aged garlic extract contains more durable and bioavailable water-soluble organosulfur components like S-allylmercapto-L-cysteine (SAMC), SAC, ajoene, alliin and allicin (Asdaq et al ., 2021; Baseggio Conrado, Fanelli, McGuire, & Ibbotson, 2021; Rais, Ved, Ahmad, & Parveen, 2021). In several studies, SAC (a phytochemical) has been documented to have antioxidant (Ruiz-Sanchez, Pedraza-Chaverri, Medina-Campos, Maldonado, & Rojas, 2020), antihepatotoxic (Anandasadagopan et al ., 2017), neurotrophic (Tobon-Velasco et al ., 2012) and anticancer (Xu et al ., 2018) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Baseggio Conrado et al examined the role of hypotaurine, an amino acid with a sulfur group, in the in vitro protection against UVA‐induced damage. They concluded that this sulfur amino acid could be an effective photoprotective ingredient in cosmetic and sunscreen formulations 8 . Hameury et al investigated a gel composed of ingredients from marine and maritime origins.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that this sulfur amino acid could be an effective photoprotective ingredient in cosmetic and sunscreen formulations. 8 Hameury et al investigated a gel composed of ingredients from marine and maritime origins. They concluded that these ingredients may prevent the visible signs of skin aging and may help keep the dermis and epidermis healthy.…”
Section: Introductionmentioning
confidence: 99%